Pemanfaatan Strategi Pemecahan Masalah untuk Meningkatkan Pemahaman Isi Bacaan di SD - Rumidjan Rumidjan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This study was intended to describe a learning model for comprehension reading in elementary school. The model implemented was problem solving strategy with IDEAL technique. The result showed that the teacher could activate students’ schemata, students could predict the content of the reading passages, identify problems and topics, explain the topics discussed, and find ideas and effect in the reading passages.